Cytomegalovirus (CMV) management in allogeneic hematopoietic cell transplantation: Pre‐transplant predictors of survival, reactivation, and spontaneous clearance. Issue 3 (5th January 2021) - Lindsay, Julian; Othman, Jad; Kerridge, Ian; Fay, Keith; Stevenson, William; Arthur, Chris; Chen, Sharon C.‐A.; Kong, David C. M.; Pergam, Steven A.; Liu, Catherine; Slavin, Monica A.; Greenwood, Matthew
Abstract: Background: Cytomegalovirus (CMV) reactivation is a frequent complication after allogeneic hematopoietic cell transplant (alloHCT). Method: We analyzed 159 alloHCT recipients with 4409 quantitative CMV viral loads to determine pre‐transplant predictors of CMV reactivation, clinically significant CMV infection (cs‐CMVi, defined as CMV viral load >1000 IU/mL), CMV disease, kinetics of spontaneous clearance of CMV, and survival using a standardized pre‐emptive therapy approach to identify at‐risk groups to target prevention strategies. Results: Cs‐CMVi was most common in D−/R+ unrelated donor transplants (URD). Spontaneous CMV clearance occurred in 26% of patients who reached a viral load of 56‐137 IU/mL, 6% at 138‐250 IU/mL and in one patient >250 IU/mL. Median time between the first CMV reactivation (>56 IU/mL) and a viral load >250 IU/mL was 13 days, whereas the time from the first viral load >250 IU/mL to reach a vial load >1000 IU/mL was 4 days. Cs‐CMVi was associated with a significant increase in non‐relapse mortality (NRM) on multivariate analysis. Conclusions: Overall, this study indicates that D−/R+ URD recipients are at high‐risk for cs‐CMVi‐ and CMV‐related mortality, and are potential candidates for targeted CMV prophylaxis. Spontaneous clearance of CMV beyond a viral load of 250 IU/mL is uncommon, suggesting that this could be used as an appropriate threshold to initiate pre‐emptive therapy.